Efficient production of anthocyanins in Saccharomyces cerevisiae by introducing anthocyanin transporter and knocking out endogenous degrading enzymes - Xu, Sha; Li, Guangjian; Zhou, Jingwen; Chen, Guicai; Shao, Jianzhong (Frontiers in Bioengineering and Biotechnology, 2022)
Anthocyanins are natural pigments found in various plants. As multifunctional natural compounds, anthocyanins are widely used in food, pharmaceuticals, health products, and cosmetics. At present, the anthocyanins are heterologously biosynthesized in prokaryotes from flavan-3-ols, which is rather expensive. This study aimed to metabolically engineer Saccharomyces cerevisiae for anthocyanin production. Anthocyanins production has been extensively studied to understand the metabolic pathway enzymes in their natural hosts, including CHS (chalcone synthase); FLS (flavonol synthase); CHI (chalcone isomerase); F3H (flavanone 3-hydroxylase); F3'H, (flavonoid 3'-hydroxylase); F3'5'H (flavonoid 3',5'-hydroxylase); DFR, (dihydroflavonol 4-reductase); ANS (anthocyanidin synthase); LAR (leucoanthocyanidin reductase); and UFGT (flavonoid 3-O-glucosyltransferase). The anthocyanin transporter MdGSTF6 was first introduced and proved to be indispensable for the biosynthesis of anthocyanins. By expressing MdGSTF6, FaDFR, PhANS0, and Dc3GT and disrupting EXG1 (the main anthocyanin-degrading enzyme), the BA-22 strain produced 261.6 mg/L (254.5 mg/L cyanidin-3-O-glucoside and 7.1 mg/L delphinidin-3-O-glucoside) anthocyanins from 2.0 g/L dihydroflavonols, which was known to be the highest titer in eukaryotes. Finally, 15.1 mg/L anthocyanins were obtained from glucose by expressing the de novo biosynthesis pathway in S. cerevisiae, which is known to be the highest de novo production. It is the first report that through the introduction of plant anthocyanin transporter and the knockout of yeast endogenous anthocyanin degrading enzyme, the anthocyanin titer has been increased by more than 100 times.